Terminação de novilhas Nelore, F1 Brangus x Nelore e F1 Braford x Nelore em confinamento - Bento, Felipe Cecconello (2018)
The objective of this study was to evaluate the nutritional and productive performance of F1 Brangus x Nelore (BGN), F1 Braford x Nelore (BFN) and Nellore (NE) heifers finishing in feedlot. Thirty heifers (10 of each genetic group) were used, with a mean age of 18 months and initial mean body weight of 265.20 ± 15.35; 255 ± 16.52 and 60.80 ± 20.19 kg, respectively. The animals received two diets during the experimental period. Initially the diet provided up to the 67 days of feedlot was composed of corn silage and concentrate, with a ratio of roughage: concentrate (V: C) of 40:60. The second diet provided from 71 days of feedlot was constituted of Panicum Hibrido cv. Massai of hay and concentrate supplied with a ratio of 30:70 V: C. Nutrideal commercial concentrate was used in both diets. The comparisons between averages of treatments were performed through orthogonal contrasts and the first one compared Nelore females with mestizo females and the second one compared mestizo females. The initial body weight was used as covariate to adjust the other variables analyzed. The heifers had lower dry matter intake (DM), organic matter (OM), crude protein (CP), extract ethereal (EE), neutral detergent soluble fiber corrected for ash and protein (NDFcp) and total digestible nutrients (TDN) that crossbred heifers BGN and BFN, BGN heifers intake more NDFcp than BFN heifers, in the other nutrients there was no difference. NE heifers intake less DM, OM and NDFcp (g / kg body weight) than crossbred heifers. BFN heifers intake less NDFcp (g / kg body weight) than BGN heifers, these genetic groups showed no difference in DM and OM intake (g / kg body weight). NE and crossbred heifers showed no differences in the apparent digestibility of DM, OM, CP, EE, NDFcp and TDN. BGN heifers showed higher apparent digestibility of NDFcp than BFN heifers, but did not difference in other nutrients. Crossbred heifers presented higher body weight at slaughter (BWS), total weight gain (TWG), daily gain of body weight (DGBW), feed efficiency (FE), warm carcass weight (WCW) and carcass length (CL) than NE heifers. Crossbred heifers presented lower carcass yield (CY) than NE heifers. NE and crossbred heifers showed no difference in carcass depth (CD). BGN and BFN heifers presented no differences regarding BWS, TWG, DGBW, FE, WCW, CY, CL and CD. BGN and BFN heifers present more fat finishing in the carcass than NE heifers. F1 Brangus x Nelore and F1 Braford x Nelore heifers present higher dietary intake, feed efficiency, productive performance, warm carcass weight, carcass length and carcass fat finishing than Nelore heifers. Genetic groups do not influence the depth of the carcass. Nelore heifers show higher carcass yield than crossbred heifers.